MULTIDISCIPLINARY MANAGEMENT, ANTI-TNF THERAPY, AND CLINICAL OUTCOMES OF INTERNALLY PENETRATING CROHN'S DISEASE COMPLICATION IN PEDIATRICS: INTERIM ANALYSES OF A MULTICENTER RETROSPECTIVE COHORT. (26th January 2023) - Constant, Brad; Okraku-Mantey, Janet; Kachelries, Kelly; Anupindi, Sudha; Huang, Jing; Baldassano, Robert; Scott, Frank; de Zoeten, Edwin; Morrow, Ryan; Ali, Sabina; Trombler, Becca; Pasternak, Brad; et al.
Abstract: BACKGROUND: Internally penetrating Crohn's disease (CD) complications (IPCDC; i.e. abscess and/or inflammatory mass) confer significant morbidity to pediatric patients with CD. Management strategies are heterogenous. Anti-tumor-necrosis-factor-a biologics (anti-TNF) are the mainstay of penetrating CD therapy and are most effective early in the treatment course. However, anti-TNF use among patients with IPCDC is limited by hesitancy concerning infectious risk. Recent studies show that this risk may be overstated. We hypothesized that early anti-TNF following IPCDC diagnosis, in the context of infection control, is 1) safe and 2) effective in pediatric patients. Here, we present interim results of an observational multi-center study. METHODS: We performed a retrospective cohort study of pediatric patients with IPCDC, across 12 tertiary children's hospitals. Patients (age 6+ years) were identified via radiology, ICD-coding, and ImproveCareNow searches. Patients admitted for an IPCDC diagnosed via MRI or CT from 2007-2021, with 1+ year of follow-up were included. Patients were excluded if complications were due to a non-CD-related process, solely perianal, if admission followed outpatient or outside institution treatment failure, or if surgery was required within 7 days of IPCDC (n=7). First, we measured the safety effect of anti-TNF following IPCDC diagnosis, prior to IPCDC resolution, on infectious serious adverse events (SAE) (i.e. new or enlarging IPCDC, or infection, requiring hospitalization or surgery), within 30 days. Next, we measured the effectiveness of anti-TNF within 30 days of IPCDC diagnosis on CD-related SAEs (i.e. non-infectious CD-related hospitalization or surgery), within one year. Kaplan-Meier curves were generated to describe outcomes over time. RESULTS: 95 patients were included. Cohort characteristics, multidisciplinary treatment strategies, and outcomes are presented in Table 1. Kaplan-Meier curves are presented in Figure 1. 80% of patients received anti-TNF within one year of IPCDC (median 37 days [IQR 7-68]). Infectious SAEs within 90 days of IPCDC occurred in 37% (median 20 days [IQR 10-26]). Among patients initiating anti-TNF prior to IPCDC resolution, 27% had an infectious SAE within 90 days, compared to 49% of those not initiating anti-TNF prior to IPCDC resolution. Non-infectious CD-related SAEs within one year occurred in 44% (median 51 days [IQR 27, 89]). Among patients initiating anti-TNF within 30 days of IPCDC, 47% had a CD-related SAE, compared to 43% in those not receiving anti-TNF within 30 days. CONCLUSION: Among a large multicenter pediatric cohort, IPCDC are associated with high rates of both infectious and CD-related SAE. Further data collection, implementation of causal inference methods, and subgroup analyses will be critical in isolating the relationship between timing of anti-TNF post-IPCDC and SAEs. Values represent Number (Percent) for categorical variables and Median (Interquartile Range) for continuous variables. Kaplan-Meier Survival Analyses for A) Infectious Serious Adverse Events and B) Crohn's Disease-Related Serious Adverse Events, stratified by exposure status. No censoring for lost-to-followup occured, as all patients had at least 1 year of follow-up avaialble.